Facilitating Better Outcomes: How Positive Species Interactions Can Improve Oyster Reef Restoration - Reeves, Simon E.; Renzi, Julianna J.; Fobert, Emily K.; Silliman, Brian R.; Hancock, Boze; Gillies, Chris L. (Frontiers in Marine Science, 2020)
Over 85% of the world's oyster reefs have been lost in the past two centuries, triggering a global effort to restore shellfish reef ecosystems and the ecosystem services they provide. While there has been considerable success in re-establishing oyster reefs, many challenges remain. These include: high incidence of failed restoration, high cost of restoration per unit area, and increasing stress from climate change. In order to leverage our past successes and progress the field, we must increase restoration efficiencies that not only reduce cost per unit area, but also increase the resilience of restored ecosystems. To help address this need, we qualitatively review the literature associated with the structure and function of oyster reef ecosystems to identify key positive species interactions (i.e., those species interactions where at least one partner benefits and no partners are harmed). We classified positive inter- and intraspecific interactions between oysters and organisms associated with oyster ecosystems into the following seven functional categories: (1) physical reef creation, (2) positive density dependence, (3) refugia from physical stress, (4) refugia from biological stress, (5) biodiversity enhancement, (6) settlement improvement, and (7) long-distance facilitation. We discuss each category of positive interaction and how restoration practitioners can use knowledge of such processes to enhance restoration success. We propose that systematic incorporation of positive species interactions into restoration practice will both enhance ecological services provided by restored reefs and increase restoration success.